ANALISIS KINERJA KEUANGAN PT. RESOURCE ALAM INDONESIA Tbk PERIODE (2014-2016) - -, Ella Dwiyanti (EKONOMIA, 2019)
This research has a purpose to determine the decline in terms of profitability ratios measured by Return of Assets, solvency ratio measured by Debt to Equity Ratio, liquidity ratio measured by Current Ratio and activity ratio measured by Total Assets Turnover, using yearly data period 2014 -2016. The theory of this research is financial management which focuses on the analysis of financial statements using four ratios, such as profitability ratio, solvency ratio, liquidity ratio, and activity ratio. Each ratio is taken 1 (one) variable, as well asÂ return of assets for profitability ratio, debt to equity ratio for solvency ratio, current ratio for liquidity ratio, and total assets turnover for activity ratio. The Analysis technique used are profitability ratios measured by Return of Assets, solvency ratio measured by Debt to Equity Ratio, liquidity ratio measured by Current Ratio and activity ratio measured by Total Assets Turnover, using 3 (three) years period of data as 2014, 2015 and 2016. The results showed: 1) return of assets decreased in 2014 and in 2016 while in 2016 it increased. 2) debt to equity ratio decreased in 2014, 2015 and 2016. 3) current ratio decreased in 2014 and increased in 2015 and as well 2016. 4) total assets turnover decreased in 2014, 2015 and 2016